Towards high efficiency inversion layer cells based on ion-charged dielectrics - Yu, M; Wright, M; Chen, J; Shi, Y; Hallam, B; Hwu, E-T; Grant, NE; Murphy, JD; Altermatt, PP; Wilshaw, P; Bonilla, RS (EU PVSEC Proceedings, 2022)
This work investigates the production and performance of p-type Inversion Layer (IL) Si solar cells, manufactured with an ion-injection technique that produces a highly charged dielectric nanolayer. Ions are applied to the front dielectric layer and then driven towards the c-Si/SiO2 interface by an electric field before stabilisation with an anneal. As this process can be performed in minutes at temperatures below 500 °C, it potentially provides a fast, yet controllable way for IL cell manufacturing. We demonstrate by simulations using Sentaurus TCAD that for the 1 ·cm p-type Si/thermal oxide model defined in this work, the sheet resistance of the field-induced electron layer can reach 1.1 k/sq in the dark by reducing band-tail interface state density to below 1014 eV-1cm-2 and increasing the dielectric charge density to above 2 × 1013 cm-2. Additionally, we present a proof-of-concept p-type IL cell on a non-gettered, non-hydrogenated substrate with an efficiency of 10.8%, and an open-circuit voltage (VOC) equivalent to that in a cell with a diffused phosphorous emitter. Lastly, we perform Sentaurus TCAD simulations to assess the efficiency potential of such IL cells. By incorporating optimal passivation, gettering, hydrogenation and metallisation, IL cells are predicted to reach an efficiency of 24.5% on 5 ·cm, and beyond 24.8% on 10 ·cm p-type substrates, provided the dielectric charge density reaches 2 × 1013 cm-2, which has been experimentally demonstrated to be possible. IL cells are therefore, in principle, a potential competitive candidate in the photovoltaic industry.